– The impact of the requirements of the business continuity in the Sustainability performance of the company relying strategy of risk management– A case Study in Al- Fayha / Basra branch Ready Construction Co limited - Hawi, Iman Askar (Journal of Economic, Administrative and Legal Sciences, 2019)
Purpose: This study is intended to improve the Sustainability performance in the Al- Fayha / Basra branch Ready Construction Co limited relationship between the strategy of risk management and requirements of the business continuity and investigation of the findings. Methodology: Making up a conceptual model of the business continuity tracks flow in the Al- Fayha / Basra branch Ready Construction Co limited The model is based on the interactive relationship between the risk management and requirements of the business continuity of Some help was available quantitative methods, relying on a combination of descriptive and quantitative approaches, in order for the accuracy of the results. results: the Al- Fayha / Basra branch Ready Construction Co limited been the subject matter of the research. It lacks the conceptual pattern that systemizes , integrates and directs its main components towards a comprehensive improvement of the company. In addition it requires relative interest in the strategic role of the strategy of risk management and its dual effects on both the business continuity and the Sustainability performance of the Company. The main recommendations were to identify the risks that affect the business continuity of the company, to control them in order to achieve full response to all business continuity requirements.